Electrophysiological remodeling in tachycardia-induced cardiomyopathy. (3rd October 2022) - Pabel, S; Knierim, M; Stehle, T; Poeppl, A; Hasenfuss, G; Maier, L; Streckfuss-Boemeke, K; Sossalla, S
Abstract: Background: Tachycardia-induced cardiomyopathy (TCM) is a reversible and likely underrecognized form of heart failure. Thus, a better understanding of the TCM-pathophysiology is warranted as the underlying early mechanisms that mediate the progression of TCM remain unclear. Purpose: This study aimed to identify the cellular mechanisms of TCM. Methods and results: Human induced pluripotent stem cell cardiomyocytes (iPSC-CM) were utilized as a translational human-based model. We performed chronic tachycardic (120 bpm) or normofrequent (control, 60bpm) cell culture pacing to study cellular changes during TCM progression. Already after 24h of tachycardic stimulation of iPSC-CM, we detected a decrease in Ca transient amplitude compared to control (Fura-2, n=49/44 cells/9 differentiations). Diastolic Ca levels and cytosolic Ca elimination were not affected after 24h of tachycardia (n=49/44/9). We detected no difference in sarcoplasmic reticulum (SR) Ca load (assessed via caffeine application) or SERCA activity (Ksys-Kcaff) after 24h of tachycardia (n=13/15/5). However, demonstrating the progress of TCM, 7d of tachycardia resulted in progressive decline of Ca transient amplitude together with an impaired Ca elimination, while diastolic Ca concentration was unchanged (n=73/66/8). These changes may underlie the reduced systolic force and impaired relaxation in TCM. We could explain these results by a significantly reduced SR Ca load and a diminished SERCA activity after 7d tachycardia (n=13/7 vs. 13/4). Using confocal microscopy (Fluo-4) we detected no difference in SR Ca spark frequency after 24h of tachycardia (n=82/66/8), while 7d of tachycardia caused an increase of Ca spark frequency (n=76/79/7), which is a typical hallmark of maladaptive remodeling in HF and likely underlie the reduced SR Ca load. Voltage clamp data of late Na current (INaL) showed no difference in INaL after 24h of stimulation (n=17/6 vs. 19/7), whereas INaL was increased after 7d of tachycardia (n=26/7 vs. 19/6). Accordingly, whole-cell current clamp experiments revealed a prolongation of the action potential after 7d of tachycardia compared to control (n=21/6 vs. 19/5), while no difference of action potential duration could be detected after 24h (n=37/31/8). Resting membrane potential and action potential amplitude were not changed. Finally, we investigated tachycardia-mediated effects on explanted human failing hearts. 8h of tachycardic stimulation (120 bpm) of human failing ventricular trabeculae already compromised systolic force, and diastolic tension and relaxation time were markedly increased compared to control (60bpm, n=8/6 trabeculae /7/6 human hearts). Conclusion: This study demonstrates that persistent tachycardia adversely alters cardiomyocyte excitation-contraction coupling via electrophysiological cellular remodeling. Our translational investigation in human myocardium may help to understand the pathophysiology of an underrated but prevalent disease. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Else Kröner-Fresenius-Stiftung (EKFS)Deutsche Gesellschaft für Innere Medizin